Analisis Kesejahteraan Masyarakat Petani Perkebunan Kelapa Sawit di Kabupaten Rokan Hulu - Rahayu, Heffi Christya; Nofriser, Nofriser; Alfiah, Lufita Nur; Gunawan, Ikhsan; Estrada, Erik; Fathoni, Ahmad (Fakultas Ekonomi Universitas Pasir Pengaraian, 2024)
Socio-economic welfare is a condition and a prosperous socio-economic life system. Welfare can be seen in terms of livelihoods, income, consumption patterns and the geographical situation of an environment or region. Community welfare can be influenced by various factors, both internal and external, so it is necessary to study the influence of these factors. This study was conducted to determine the effect of consumption, income, and health factors on the welfare of oil palm plantation farmers in Rokan Hulu Regency. The method used is simultaneous and partial tests on each variable. The results of this study indicate that (1) simultaneously, the income, consumption, and health variables have a significant effect on the welfare variable, (2) partially, the income variable has a positive and significant effect on the welfare variable, (3) partially the consumption variable has no effect on the welfare variable, and (4) partially the health variable has a positive and significant effect on the welfare variable.